Employment Precarity, COVID-19 Risk, and Workers' Well-Being During the Pandemic in Europe. Issue 2 (May 2023) - Wu, Qiong (Miranda)
The COVID-19 crisis highlights a growing precarity in employment and the importance of employment for workers' well-being. Existing studies primarily examine the consequences of employment precarity through non-standard employment arrangements or the perception of job insecurity as a one-dimensional measure. Recent scholars advocate a multidimensional construct with a wide range of objective and subjective characteristics of precariousness. Using data from Eurofound's Living, Working, and COVID-19 surveys, I define employment precarity as the objective form of employment instability, as well as subjective terms of job insecurity and emotional precariousness. I also investigate whether and how various facets of employment precarity along with COVID-19 risk are associated with workers' mental and subjective well-being across 27 European Union member states during the pandemic. This study sheds light on a comprehensive understanding of objective and subjective dimensions of employment precarity, as well as their effects on workers' well-being during the COVID-19 pandemic.